THE COOL GALACTIC R Coronae BOREALIS VARIABLE DY Persei - Zacs, L. (Одеські астрономічні публікації, 2017)
DY Per (CGCS 372) was suspected to be an R CrB star based on the photometry by Alksnis (1994). Subsequent photometric monitoring revealed a number of sudden light declines typical for R CrB variables superimposed on the 792-day cycle of long-period light variations (Alksnis et al. 2002). However, the temperature of this star is much lower than average for other R CrB stars. Moreover, the luminosity of DY Per was suspected to be lower than usually for R CrBs. Keenan & Barnbaum (1997) estimated Teff ≃ 3500 K using the standard criteria of spectral classification and a giant luminosity. DY Per was classified as R8, C4,5, C5,4p, and C-Hd 4.5 C26 (Keenan & Barnbaum, 1997). Alcock et al. (2001) revealed four stars similar to the Galactic variable DY Per among eight RCBs discovered in the Large Magellanic Cloud.